Innovation Strategies: A SWOT-Based Approach to Strengthening Micro, Small, and Medium Enterprises (MSMEs) Marketing in Tlemang Village, Indonesia - Rachman, Audi Faradilla; Isbandono, Prasetyo; Lestari, Yuni (Universitas Negeri Surabaya, 2024)
Micro, Small, and Medium Enterprises (MSMEs) in Tlemang Village, Ngimbang District, Lamongan Regency Indonesia, have difficulties in marketing and do not yet have appropriate methods for marketing products. This research aims to determine the business conditions in Tlemang Village MSMEs and analyze appropriate product marketing methods that Tlemang Village MSMEs can carry out. The focus of this research uses SWOT analysis. This article uses a descriptive research method with a qualitative approach. The data sources in this article come from primary data, namely interviews and observations, as well as secondary data from previous research and relevant articles. The data analysis technique in this research uses an interactive model by Miles and Huberman with components of data reduction, data presentation, and drawing conclusions. The results of this research using SWOT analysis can use the following strategies: SO strategy: maintain and improve product quality, improve human resource quality, improve product marketing; WO strategy: increase product innovation, open new target markets so that sales are wider, market products in offline and online stores; ST strategy: increase product promotion activities to the public, maintain stability in product selling prices; WT strategy: expand market network, create packaging that attracts consumers, find the right method for marketing activities. As a recommendation, the local government should support MSMEs in Tlemang Village in adopting innovations such as digital collaboration, affordable quality control tools, and participation in business incubation programs.